From the Editor - Aves Editorial, Aves Editorial (Cerrahpaşa Medical Journal, 2023)
Dear Readers, In the last issue of 2023 we have some distinguished articles. You can find at page 243, a prospective eletrophysiological study which shows that Diabetes can lead to subclinical vagal neuropathy (Taskıran 2023). We have an important study about the the long term results of medullary tyroid carcinoma (Kara 2023, page 247), this retrospective study shows that calcitonin can be a prognostic factor at the third month in the postoperative period. If you want to get some clues about the management of invasive mold infection in hematological malignany we can recommend you the study of Ozdemir (page 253). We have also a study about the etiological factors about the neonatal convulsion (Gungor 2023, page 259) and an study about palatine tonsil imaging with cervical ultrasonography (Bozbeyoglu 2023 page 302). There are a total of 17 orginal articles in this issue, you may also be interested to read a case of bilateral corpus collosum infarction in the image of interest section. I wish you a happy new year. Editor-in-Chief Ali İbrahim HATEMİ